(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study aims to develop a systematic review of the influence of agricultural financing awareness and access to microfinance credit on financial challenges among agricultural entrepreneurs from both global and Philippine perspectives. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework was used as a guideline to ensure methodological rigor and transparency in the systematic literature review process. Scholarly articles published between 2015 and 2025 were examined, and 20 empirical studies that met the inclusion criteria were selected for analysis. The findings reveal that both agricultural financing awareness and access to microfinance credit play significant roles in reducing financial challenges, enhancing financial resilience, and improving decision-making among agricultural entrepreneurs. However, the review also identified inconsistencies in the strength of these relationships across different contexts, as well as a limited number of studies exploring their combined effects. These gaps highlight the need for further research to validate and extend existing findings across diverse agricultural settings. Research examining the combined effects of agricultural financing awareness and access to microfinance credit on financial challenges remains limited, particularly in the context of developing countries like the Philippines. This study contributes by synthesizing recent empirical evidence and proposing a more comprehensive conceptual understanding of how financial literacy and credit access jointly influence the financial sustainability of agricultural enterprises.